Hydrogen supply chain architecture for bottom-up energy systems models. Part 1: Developing pathways - Bolat, Pelin; Thiel, Christian (International journal of hydrogen energy, 2014)
The integration of hydrogen energy systems in the overall energy system is an important and complex subject for hydrogen supply chain management. The efficiency of the integration depends on finding optimum pathways for hydrogen supply. Accordingly, energy systems modelling methods and tools have been implemented to obtain the best configuration of hydrogen processes for a defined system. The appropriate representation of hydrogen technologies becomes an important stage for energy system modelling activities. This study, split in consecutive parts, has been conducted to analyse how representative hydrogen supply pathways can be integrated in energy systems modelling. The current paper, the first part of a larger study, presents stylised pathways of hydrogen supply chain options, derived on the basis of a detailed literature review. It aims at establishing a reference hydrogen energy system architecture for energy modelling tools. The subsequent papers of the study will discuss the techno-economic assumptions of the hydrogen supply chain components for energy modelling purposes.